Understanding the meaning of the concept of old age in modern social and psychological studies (Actual Problems of Psychology in Educational Institutions, 2019)
In the article, the author analyzes the understanding of themeaning of the concept of old age in modern socio-psychological researchbased on: 1) the definition of the concept of old age and psychophysiologicalchanges occurring at this stage of human development; 2) the formation ofpersonality at this stage of age development; 3) the attitude of the aging personherself to the changes that occur to her, and 4) the stereotypes and socialattitudes of modern society regarding old age and aging. The study concludesthat research of the concept of old age is at the present stage of development ofsociety one of the important ways to optimize interaction and social relationsbetween people of different generations, as well as an important factor in theconstructive psychosocial development of a person in the late period of his life.
Keywords: old age, aging, aging person, psychophysiological changes, stereotypes regarding old age and aging, social attitudes regarding old age and aging